Studi Organisme Pengganggu Tanaman pada Bit Merah (Beta vulgaris L.) yang Dibudidayakan Dalam Greenhouse Dataran Rendah - Aisyah, Mahindra Dewi Nur; Akhiriana, Enik; Hamawi, Mahmudah (Rekayasa, 2023)
Beet (Beta vulgaris L) is a potential plant for producing sugar (sugar beet) and dye (beetroot). Therefore, there is a great opportunity to be cultivated in Indonesia because of the suitable climate. Beet plants can harvest twice a year and have a higher yield than in areas with subtropical climates. However, the presence of plant pests and disease organism attacks can be a limiting factor in beet production. This study aims to observe pests and diseases attack beet cultivated in greenhouses. The observation conducted for five months, from September 2022 to January 2023. The results showed that symptoms of pest and disease attacks beet are Spodoptera sp., Lyriomyza sp., tungau, Cercospora sp., Rhozoctonia sp., and Erysiphe sp.